Finding Meaning in Disappointment: The Integration of Tafakkur and Tadzakur as Adolescent Emotional Regulation Strategies in Islamic Psychology - Aziz, Akbar Nur; Halim Purnomo; Fuad Nashori; Fitriah M. Suud (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2025)
Disappointment is one of the most prevalent negative emotions experienced by adolescents and can disrupt psychological well-being if not properly managed. This study aims to develop an integrative Islamic model of emotion regulation based on the Qur’anic concepts of tafakkur (cognitive reappraisal) and tadzakkur (spiritual meaning-making). Employing a qualitative approach, this research employed a literature study method and a thematic analysis of Qur’anic verses containing the expressions